Dithiolane quartets: thiol-mediated uptake enables cytosolic delivery in deep tissue. Issue 41 (6th October 2021) - Martinent, Rémi; Tawffik, Salman; López-Andarias, Javier; Moreau, Dimitri; Laurent, Quentin; Matile, Stefan
Abstract : Cytosolic delivery in multicellular 3D spheroids is shown to be an intrinsic advantage of thiol-mediated uptake, which is compatible with proteins and QDs, achieving targeting and controlled release. Abstract : The cytosolic delivery of various substrates in 3D multicellular spheroids by thiol-mediated uptake is reported. This is important because most orthodox systems, including polycationic cell-penetrating peptides, fail to deliver efficiently into deep tissue. The grand principles of supramolecular chemistry, that is the pH dependence of dynamic covalent disulfide exchange with known thiols on the transferrin receptor, are proposed to account for transcytosis into deep tissue, while the known but elusive exchange cascades along the same or other partners assure cytosolic delivery in kinetic competition. For quantitative detection in the cytosol, the 2D chloroalkane penetration assay (CAPA) is translated to 3D deep tissue. The targeted delivery of quantum dots, otherwise already troublesome in 2D culture, and the controlled release of mechanophores are realized to exemplify the power of thiol-mediated uptake into spheroids. As transporters, dithiolane quartets on streptavidin templates are introduced as modular motifs. Built from two amino acids only, the varied stereochemistry and peptide sequence are shown to cover maximal functional space with minimal structural change, i.e., constitutional isomers. Reviving a classic in peptide chemistry, this templated assembly of β quartets promises to expand streptavidin biotechnology in new directions, while the discovery of general cytosolic delivery in deep tissue as an intrinsic advantage further enhances the significance and usefulness of thiol-mediated uptake.